Concept of Operations as a Boundary Object for Knowledge Sharing in the Design of Robotic Swarms - Jari Laarni; Hanna Koskinen; Antti Väätänen (Association for Scientific Computing Electronics and Engineering (ASCEE), 2022)
Designing a swarm of autonomous robots for commercial, military, or other purposes is a challenging engineering and human factors design effort. The challenges argue in favor of practices and tools for better integration of different engineering disciplines and for the advancement of communication between stakeholders with different interests. The Concept of Operations (ConOps) approach is widely used in Systems Engineering for this purpose. A ConOps is a high-level description of how the elements of a system and entities in its environment interact in order to achieve their stated goals. This paper will present the development of a ConOps for a swarm of autonomous robotic vehicles in the military domain to demonstrate how autonomic robotic swarms can be deployed in different military branches in the future. The proposed ConOps can be considered as a boundary object in the design, validation, or procurement of an autonomous robotic swarm system. We also propose that the ConOps should be maintained throughout the system life-cycle as an overview description and definition of overall goals and policies.